Network routing : algorithms, protocols, and architectures - Medhi, Deepankar; Ramasamy, Karthik (Morgan Kaufmann, 2018)
Network Routing: Algorithms, Protocols, and Architectures, Second Edition, explores network routing and how it can be broadly categorized into Internet routing, PSTN routing, and telecommunication transport network routing. The book systematically considers these routing paradigms, as well as their interoperability, discussing how algorithms, protocols, analysis, and operational deployment impact these approaches and addressing both macro-state and micro-state in routing. Readers will learn about the evolution of network routing, the role of IP and E.164 addressing and traffic engineering in routing, the impact on router and switching architectures and their design, deployment of network routing protocols, and lessons learned from implementation and operational experience. Numerous real-world examples bring the material alive. Extensive coverage of routing in the Internet, from protocols (such as OSPF, BGP), to traffic engineering, to security issues A detailed coverage of various router and switch architectures, IP lookup and packet classification methodsA comprehensive treatment of circuit-switched routing and optical network routingNew topics such as software-defined networks, data center networks, multicast routingBridges the gap between theory and practice in routing, including the fine points of implementation and operational experienceAccessible to a wide audience due to its vendor-neutral approach.